The Influence Of Financial Technology Development, Social Environment, And Hedonistic Lifestyle On The Ability To Manage Finances - Siti Ahdina Saadatirrohmi (Pt. Anagata Sembagi Education, 2024)
This study aims to examine the impact of financial technology development, social environment, and hedonistic lifestyle on the financial management ability of FEBI UIN Mataram Indekos students. The research adopts an associative approach and employs quantitative methods. The population of this study consists of 453 active Indekos students from FEBI UIN Mataram, class of 2021-2022. Using Probability Sampling with a Random Sampling technique, the study selected 82 respondents. Data analysis was conducted using multiple linear regression tests with SPSS version 26. The results reveal that the social environment has a significant partial effect on students' financial management ability. However, financial technology development and a hedonistic lifestyle did not show a significant individual impact on financial management ability. On a broader scale, the study found that all three variables—financial technology development, social environment, and hedonistic lifestyle—collectively have a significant effect on financial management ability. These findings suggest that while the social environment plays a crucial role, other factors like financial technology and lifestyle choices also influence students' ability to manage finances.